Nuclear Targeted Peptide Combined With Gambogic Acid for Synergistic Treatment of Breast Cancer - Dang, Wenli; Guo, Pan; Song, Xunan; Zhang, Ying; Li, Nan; Yu, Changxiang; Xing, Bin; Liu, Rui; Jia, Xintao; Zhang, Qingqing; Feng, Xiaojiao; Liu, Zhidong (Frontiers in Chemistry, 2022)
As a natural compound, gambogic acid (GA) emerged a shining multi-target antitumor activity in a variety of tumors. Whereas its poor solubility and non-specific effect to tumor blocked the clinical application of this drug. Herein, we reported a simple and effective strategy to construct liposome modified with nuclear targeted peptide CB5005N (VQRKRQKLMPC) via polyethylene glycol (PEG) linker to decrease the inherent limitations of GA and promote its anti-tumor activity. In this study, liposomes were prepared by thin film hydration method. The characterization of formulations contained particle size, Zeta potential, morphology and encapsulation efficiency. Further, in vitro cytotoxicity and uptake tests were investigated by 4T1 and MDA-MB-231 cells, and nuclear targeting capability was performed on MDA-MB-231 cells. In addition, the in vivo antitumor effect and biological distribution of formulations were tested in BALB/c female mice. The GA-loaded liposome modified by CB5005N showed small size, good uniformity, better targeting, higher anti-tumor efficiency, better tumor inhibition rate and lower toxicity to normal tissues than other groups. In vitro and in vivo research proved that CB5005N-GA-liposome exhibited excellent anti-tumor activity and significantly reduced toxicities. As a result, CB5005N-GA-liposome nano drug delivery system enhanced the tumor targeting and antitumor effects of GA, which provided a basis for its clinical application.